1973
DOI: 10.1136/pgmj.49.578.845
|View full text |Cite
|
Sign up to set email alerts
|

Further observations from an experience of 660 cases of stereotactic tractotomy

Abstract: SummaryA study of the results of some 660 cases of stereotactic tractotomy shows that these have been consistent through a 12-year period, more than 50°4 of cases of resistant depression can be set free of medical care and another 25%4 at least can be improved. Comparable results are also obtained in obsessional illness and anxiety states, particularly those in which there is a depressive component.The original localization of the target site described in 1964 has not required modification but pathological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…By 1973, this procedure had been performed in over 650 cases of major depression, OCD, or anxiety with reported success rates around 50% (Knight, 1973). In 1994, Bridges and colleagues reviewed 1300 cases of subcaudate tractotomy treating anxiety, phobic anxiety, OCD, MDD, or bipolar disorder (Bridges et al, 1994).…”
Section: Outcomes After Ablationmentioning
confidence: 99%
“…By 1973, this procedure had been performed in over 650 cases of major depression, OCD, or anxiety with reported success rates around 50% (Knight, 1973). In 1994, Bridges and colleagues reviewed 1300 cases of subcaudate tractotomy treating anxiety, phobic anxiety, OCD, MDD, or bipolar disorder (Bridges et al, 1994).…”
Section: Outcomes After Ablationmentioning
confidence: 99%
“…Subcaudate tractotomy (SCT) was introduced by Geoffrey Knight in 1964 and aims to selectively interrupt white matter tracts connecting the orbitofrontal cortex and subcortical limbic structures. The target is an area inferior to the head of the caudate nucleus overlying area 13 of the orbitofrontal cortex, which posteriorly includes the substantia innominata [78,79]. Originally, Knight adopted a freehand technique for implanting bilateral B-emitting yttrium 90 ( 90 Y) seeds.…”
Section: Subcaudate Tractotomymentioning
confidence: 99%
“…By 1973, Knight's procedure had been performed in more than 650 cases of MDD, OCD, or anxiety with success rates around 50%. 22 In 1994, Bridges and colleagues reviewed 1300 cases of subcaudate tractotomy used to treat anxiety, phobic anxiety, OCD, MDD, or bipolar disorder. 23 They concluded that 40 to 60% of patients benefited from the procedure to the point of living normal or near-normal lives.…”
Section: Subcaudate Tractotomymentioning
confidence: 99%